Pengaruh Environmental, Social, and Governance (ESG) Disclosure dan Enterprise Risk Management (ERM) terhadap Nilai Perusahaan Subsektor Makanan dan Minuman - Yudiansyah, Rizky; Burhany, Dian Imanina (Indonesian Accounting Literacy Journal, 2025)
This study aims to analyze the impact of environmental, social, and governance (ESG) disclosure and enterprise risk management (ERM) on firm value in food and beverage sub-sector companies, both partially and simultaneously. This research employs a quantitative approach, utilizing secondary data in the form of sustainability and annual reports for the selected periods. The independent variables include ESG disclosure, measured by the ESG disclosure index, and ERM, measured by the ERM index. The dependent variable is firm value measured by price to book value (PBV). The analysis was conducted on food and beverage sub-sector companies listed on the Indonesia Stock Exchange, selected using purposive sampling criteria, specifically those that have published sustainability reports for the 2021-2023 period. The research hypothesis was tested using multiple linear regression analysis. The findings of this study indicate that ESG disclosure has a significant negative impact on firm value, ERM does not have a significant impact on firm value, and ESG disclosure and ERM together influence the firm value.